Проблеми імплементації позитивного зарубіжного досвіду правового регулювання моральних та матеріальних заохочень поліцейських у вітчизняні реалії - Балик, С. О.; Balyk, S. O. (Юридична наука. - 2020. - № 6 (108). - С. 263-270, 2020)
Узагальнено позитивний зарубіжний досвід правового регулювання моральних та матеріальних заохочень поліцейських на прикладі: Сполучених Штатів Америки, Канади, Республіки Молдова, Республіки Литва та Республіки Білорусь. Визначено пріоритетні напрями зарубіжного досвіду, який доречно перейняти в межах національних реалій з метою удосконалення механізму застосування матеріальних та моральних заохочень до працівників Національної поліції України.

The purpose of the article is to summarize the foreign experience of material and moral encouragement of police officers and to study the possibilities of its use in Ukraine. The article, based on the analysis of scientific views of scientists, summarizes the positive foreign experience of legal regulation of moral and material incentives for police officers on the example of the United States, Canada, the Republic of Moldova, the Republic of Lithuania and the Republic of Belarus. Priority areas of foreign experience have been identified, which should be adopted within the framework of national realities in order to improve the mechanism of application of material and moral incentives to employees of the National Police of Ukraine. It is concluded that today it is possible to distinguish three models of organization of the system of incentives for police officers, in each of which the ratio of moral and material incentives for police officers has a different format. According to the first model (USA), employee incentives as such do not exist. That is, within the activities of the police, employment incentives are provided by providing law enforcement officers with high social benefits and guarantees of their employment, as well as the widespread use of bonuses based on systematic evaluation of performance of this category of workers. The second model of organizing the system of incentives for police officers (Canada, France, Lithuania) provides a wide range of incentives that can be applied to police officers, the central place among them is material incentives that improve the property of law enforcement officers. At the same time, the experience of the Republic of Lithuania should be singled out, where a unique system of «self-sufficiency» of the law enforcement structure has been formed. The legislation of this state allows additional funding for police activities through the provision of police services, as well as fines.

Обобщен положительный зарубежный опыт правового регулирования моральных и материальных поощрений полицейских на примере Соединенных Штатов Америки, Канады, Республики Молдова, Республики Литва и Республики Беларусь. Определены приоритетные направления зарубежного опыта, который уместно перенять в пределах национальных реалий с целью усовершенствования механизма применения материальных и моральных поощрений к работникам Национальной полиции Украины.
Problems of implementation of positive foreign experience of legal regulation of moral and material incentives of police officers in domestic realities
Балик, С. О. Проблеми імплементації позитивного зарубіжного досвіду правового регулювання моральних та матеріальних заохочень поліцейських у вітчизняні реалії / Балик С. О. // Юридична наука. - 2020. - № 6 (108). - С. 263-270. - DOI: https://doi.org/10.32844/2222-5374-2020-108-6-1.32.
Балик , С. О. (2020). ПРОБЛЕМИ ІМПЛЕМЕНТАЦІЇ ПОЗИТИВНОГО ЗАРУБІЖНОГО ДОСВІДУ ПРАВОВОГО РЕГУЛЮВАННЯ МОРАЛЬНИХ ТА МАТЕРІАЛЬНИХ ЗАОХОЧЕНЬ ПОЛІЦЕЙСЬКИХ У ВІТЧИЗНЯНІ РЕАЛІЇ. Юридична наука, (6(108), 263–270. https://doi.org/10.32844/2222-5374-2020-108-6-1.32.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поліцейські; police officers; полицейские; зарубіжний досвід; foreign experience; зарубежный опыт; матеріальні заохочення; material incentives; материальные поощрения; моральні заохочення; moral incentives; моральные поощрения; правове регулювання; legal regulation; правовое регулирование